The Role of Intellectuals in the State-Society Nexus (Book collections on Project MUSE., 2016)
"If we are to talk about a 'new' intellectual movement, the question is begged: what happened to the 'old' intellectual movement? What happened to the thinkers who inspired and led our struggle against colonialism, apartheid and exploitation? What has happened to the thinkers who gave substance and guidance and, in many cases, practical leadership to our attempts to undo the past and forge a new future? In pursuit of answers to these questions, the Mapungubwe Institute for Strategic Reflection (MISTRA), in partnership with Liliesleaf Trust, hosted a roundtable in March 2015 with the theme 'The Role of Intellectuals in the State-Society Nexus'. Inputs were provided by a range of thinkers, including Ibbo Mandaza, Ben Turok, Ari Sitas, Ayanda Ntsaluba, Xolela Mangcu, Joel Netshitenzhe, Tshilidzi Marwala and Nomboniso Gasa, as well as provocative and piercing contributions from the attendees. This publication aims to put the inputs and debates at the roundtable further into the public domain, and simply records the contributions of the main speakers, the respondents, as well as the discussion from the floor."--Back cover